Evidence-based guidelines, time-based health outcomes, and the Matthew effect - Essink-Bot, Marie-Louise; Kruijshaar, Michelle E; Barendregt, Jan J; Bonneux, Luc G A (European journal of public health, 2007)
Background: Cardiovascular risk management guidelines are ‘risk based’; health economists' practice is ‘time based’. The ‘medical’ risk-based allocation model maximises numbers of deaths prevented by targeting subjects at high risk, for example, elderly and smokers. The time-based model maximises numbers of life years gained by treating the young and non-smokers, or ‘the one who has will be given more’ (Matthew 25:29). We explored practical consequences of risk- or time-based allocation. Methods: We used epidemiological modelling to generate semi-quantitative scenarios comparing the distributional effects of allocating a fixed number of prescriptions of a (hypothetical) preventive cardiovascular drug (‘CVStop’) either to avert the maximum number of deaths (risk-based) or to save the maximum number of life years (time based) in the male Dutch population. We subsequently asked 123 Dutch guideline developers which distribution they preferred. Results: Time- and risk-based allocations resulted in different distributions of the drug across the population. There were also differences in absolute numbers of life years gained and deaths averted, and in the distribution of these across the population. For example, risk-based allocation of ‘CVStop’ resulted in preferential treatment of elderly, leading to more deaths averted (mostly among 70 and above) but fewer life years gained, if compared with time-based allocation. The guideline developers experienced the choice dilemmas as difficult. No priority choice was dominant among the respondents. Conclusion: In evidence-based resource allocation the choice to save time or to avert deaths may introduce moral choices because of the various origins of increased disease risk. Evidence-based guideline development inevitably has moral implications.